Effects of Cultivation Techniques and Plot Levels on Growth, Yield and Yield Components of Lowland Rice Grown on Acid Sulfate Soil for Sustainable Production - Tun, Phyu Thaw; Thobunluepop, Pitipong; Sarobol, Ed; Sreewongchai, Tanee (Agriculture and Natural Resources, 2015)
The effects of different cultivation techniques and plot levels on the productivity of lowland rice grown on acid sulfate soil were examined and a field experiment was conducted in Pathum Thani province, Thailand. Cultivation technique (modified cultivation (MC) technique and conventional cultivation (CC) technique) and plot level (upper plot and lower plot) were the experimental factors. Under the MC technique, the farmer applied 187.5 kg.ha-1 of compound fertilizer (16-20-0) and 18.75 kg.ha-1 of KCl (0-0-60) at planting, incorporated the previous rice stubble and transplanted the rice seedlings, followed by 2 wk flooding and 1 wk of complete drainage both throughout the growing period. Under the CC technique, the farmer applied 312.5 kg.ha-1 of compound fertilizer (16-20-0) at planting, burned the previous rice stubble and broadcast rice seeds followed by continuous flooding throughout the growing period. The upper plot was directly irrigated from a drainage canal whereas the lower plot was irrigated with the drained water from the upper plot. Compared with the CC technique, the MC technique produced significantly higher grain yield, yield components, leaf area index, plant dry weight, net assimilation rate and harvest index. The upper and lower plots had no observed effect on most yield components and plant growth parameters. Overall, the results suggested that farmers should follow the MC technique to produce a higher rice grain yield along with the improvement of soil properties such as soil pH, cation exchange capacity and organic matter and to achieve economically, environmentally and socially sustainable lowland rice production in acid sulfate soil over the long term.